PENJERAPAN ZAT WARNA SINTETIS MENGGUNAKAN KARBON AKTIF KELAPA SAWIT DAN PENGEMBANGANNYA SEBAGAI BAHAN AJAR - Efa Susanti; M.Lutfi Firdaus; Sumpono Sumpono (University of Bengkulu, 2017)
This study aims to: (1) explain the ability of the active carbon absorption of Palm Oil Palm as a dye adsorbent Reactive Red and Direct Green (2) determines the pH, contact time, and weight of the optimum adsorbent and the influence of temperature using activated carbon. Reactive Red and Direct Green dyestuffs. (3) to explain the influence of video media usage on the improvement of learning result and critical thinking ability of students in Chemistry class XI MIPA E at SMAN 2 Kota Bengkulu. The procedure in this study is the activation of activated carbon of palm oil and activated, activated carbon characterization using FTIR, Determination of maximum wavelength (?), Calibration curve creation, Adsorption of substance by activated carbon of palm oil: determining pH, contact time, adsorbent weight, , adsorption isotherms, Determination of temperature effect, Adsorption Isotherm Determination, Determination of adsorption kinetics, Applications on dyestuffs. The data were analyzed. The result of pH variation, variation of adsorbent weight, and contact time were made curve so that pH, adsorbent weight, concentration and optimum contact time were obtained using Excel program. Using ANAVA one way, followed by KR-20 test and one sample t test. The results showed that there were: reactive red optimum wavelength 496 nm, optimum pH 3, optimum time 40 min, absorbent weight 150 mg, maximum absorbency KAPKS 32,73 mg / gr and direct green optimum wavelength 613 nm, with optimum pH 5, optimum time 40 minutes, absorbent weight 150 mg, maximum absorbency KAPKS 32.825 mg / gr. there is an increase of chemistry learning outcomes during the enrichment hours or outside of class hours and critical thinking skills of grade XI IPA E SMAN2 Kota Bengkulu using audio-visual media with average pretest score of 75 and average post test score 82.27 with four criteria critical thinking skills are less critical by 26%, critical enough 43%, critical 23% and very critical at 8%.